FACTORS INFLUENCING FERTILITY IN LAPAROSCOPIC ARTIFICIAL INSEMINATION IN SHEEP. - Bergstein-Galan, Tacia Gomes; Weiss, Romildo Romualdo; Camargo, Carlos Eduardo; Kozicki, Luiz Ernandes (Archives of Veterinary Science, 2022)
Fertility following artificial insemination (AI) programs in sheep is affected by many variables. The aim of this study was to identify extrinsic (year, season), intrinsic (age and breed) and AI procedure related (number of AIs, synchronization protocols, semen preservation method) factors that influence fertility after laparoscopic AI in sheep. Data from 159 laparoscopic AI procedures were categorized according to year (from 2013 to 2017), season (Winter, Spring, Summer and Autumn), breed (Dorper, White Dorper, Texel, Cross-breed), age in months (≤12, 13-24, 25-36, 37-48, ≥49), estrus synchronization protocol (short-term or long-term), cumulative number of AIs (1 to 4) and semen preservation method (frozen or fresh). Frequency analysis using chi-square test was used. Year, age, number of AIs and synchronization protocols did not influence fertility after laparoscopic AI in sheep. Fertility was higher (P<0.05) in sheep inseminated in spring (64.28%) and summer (54.16%) when compared to winter (36.92%) and autumn (32.14%). Dorper breed fertility (58.02%) was higher (P<0.05) than White dorper (25%) and Cross-breed (30.23%). There was a lower (P<0.05) pregnancy rate in sheep inseminated with frozen semen (38.27%) than sheep inseminated with fresh semen (53.84%). In conclusion, season, breed and semen preservation method can influence fertility in sheep after laparoscopic AI.